Pengembangan E-Book untuk Meningkatkan Kemampuan Peserta Didik dalam Membuat Puff Pastry - Nasution, Tri Anita; Ampera, Dina; Farihah, Farihah (LPPM Institut Pendidikan Nusantara Global, 2025)
This research and development study aims to produce an E-Book learning material using the Flipbook Maker application that is feasible, practical, and effective in enhancing students' skills in making puff pastry. This study follows the ADDIE development model, which consists of five stages: (1) the Analysis stage to conduct a preliminary study, (2) the Design stage to develop the e-book, (3) the Development stage to refine the e-book and validate it with experts, (4) the Implementation stage to conduct user trials, and (5) the Evaluation stage to assess and improve the quality of the e-book. The research findings indicate: (1) Validation by instructional material experts classified the puff pastry e-book as highly feasible, with an average score of 95.14%. (2) Validation by media experts also classified it as highly feasible, with an average score of 90.97%. (3) Validation by instructional design experts rated it as highly feasible, with an average score of 96.35%. (4) Individual trials categorized it as highly feasible, with an average score of 88.83%. (5) Small group trials also placed it in the highly feasible category, with an average score of 85.45%. (6) Field trials classified it as very good, with an average score of 86.24%. The practicality test conducted by subject teachers resulted in an average score of 91.67% (highly practical), while the student practicality test scored an average of 94.24% (highly practical). The effectiveness test of students' practical skills in making puff pastry showed that students in the experimental class who used the e-book puff pastry achieved an average practical score of 37.7, whereas students in the control class who used printed book obtained an average score of 35. The normality test results for the experimental class indicated that χ²calculated < χ²table (5.02 < 11.07), and for the control class, χ²calculated < χ²table (2.68 < 11.07), suggesting a normal distribution at a 5% significance level. The homogeneity test showed that Fcalculated < Ftable (0.99 < 4.14), indicating that the data distribution was homogeneous. The hypothesis test using an Independent t-test resulted in tcalculated > ttable (7.8 > 1.9), leading to the rejection of Ho and acceptance of Ha. This indicates that there is a significant difference in the practical results of students using the E-Book Puff Pastry in the experimental class compared to the practical results of students using printed books in the control class of Grade XI Culinary Arts at SMK Negeri 8 Medan.